Precision attachment with intraradicular post in bilateral free end edentulous - Dimas Anggayuno Dwi Prabowo; Gandis Harumi; Endang Wahyuningtyas (Indonesia Prosthodontic Association, 2023)
Loss of the molar on both sides can interfere with the important process of mastication and affect the shape of the face, that is greatly interferes mastication process. Therefore, dentures must be replaced immediately. A 63-years-old female complained about her dentures because they feel loose and uncomfortable. The patient lost teeth 16-11, 21-27, 34, 35, 46, and 47. The jaw lost its occlusal support. Loss of the posterior teeth on both sides of the man-dible condition; the teeth with a strong grip are the indication to make a removable denture with precision attach-ments. The treatment is a removable denture with an upper and lower metal frame with a retention ball attachment. First, fiber posts were installed on teeth 45, which have been endodontically treated. Then, teeth 34, 35, 44, and 45 were prepared, and a crown was made with a ball attachment handle as male part on the posterior part of the porcelain fused to metal. It is concluded that the patient is satisfied with her new denture, feels more comforta-ble chewing, and the appearance was much better than before.